2002
DOI: 10.1046/j.1523-5378.2002.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

A Population‐Based Survey on Gastrointestinal Tract Symptoms and Helicobacter pylori Infection in Children and Adolescents

Abstract: Dyspeptic symptoms are frequent in children, and its association with H. pylori infection is more evident than with recurrent abdominal pain. The age at which the infection is acquired seems to be under 6 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…A large number of reports have been produced on H. pylori and showed that it is able to infect at least 50 % of the world's population (Perry et al 2006) especially in their early life (Sabbi et al 2008) and persists throughout the rest of their lifetime. According to (Melake et al 2012;De Giacomo et al 2002) 63.3-70 % of children were infected by H. pylori at/before 14 and 15 of age revealing high rate of infection at the first and second decades. The most common route of transmission is person-person contact, by either the oral-oral route or the fecal-oral route (Brown 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of reports have been produced on H. pylori and showed that it is able to infect at least 50 % of the world's population (Perry et al 2006) especially in their early life (Sabbi et al 2008) and persists throughout the rest of their lifetime. According to (Melake et al 2012;De Giacomo et al 2002) 63.3-70 % of children were infected by H. pylori at/before 14 and 15 of age revealing high rate of infection at the first and second decades. The most common route of transmission is person-person contact, by either the oral-oral route or the fecal-oral route (Brown 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among otherwise healthy school children, 3.5%–27% have dyspepsia,1,2 6%–14% have irritable bowel syndrome,3 and up to 8% have functional constipation 4. In children with neurologic disorders, gastrointestinal dysfunction is even more common.…”
Section: Introductionmentioning
confidence: 99%
“…H pylori is almost always acquired in childhood (usually before age 10 years), 9 and, if untreated, infection is lifelong. In the developing world, up to 70% of children are infected with H pylori by age 15 years ( Figure 1).…”
Section: Infection With H Pylori: Risk Factors and Acquisitionmentioning
confidence: 99%
“…Because of radioactivity risks, particularly in children, there are very few data on the use of 14 C-labeled urea breath tests in the pediatric population. Although the UBT has been studied in children, 9,[19][20][21][22] its diagnostic ability, especially in those younger than 3 years of age, may be limited by several factors. For example, performance of the test requires some level of oral-pharyngeal coordination, with children being more likely to retain the compound in the oropharynx that also harbors urease-producing organisms, thereby producing false-positive test results.…”
Section: Diagnosing H Pylori In Childrenmentioning
confidence: 99%